Respuesta :
First, simplify this equation as much as you can.
5 + 6y = 9y + 2 + 3(1 - y)
Use the distributive property on the 3(1 - y) part.
3 • 1 = 3
3 • -y = -3y
5 + 6y = 9y + 2 + 3 + -3y
Combine like terms.
The like terms are:
9y and -3y
2 and 3
9y - 3y = 6y
2 + 3 = 5
5 + 6y = 6y + 5
This can not be simplified further, since doing so would only result in 0.
So no matter what y is, this is true.
If you were to fully simplify this, it would be 0 = 0.
Hope this helps!
5 + 6y = 9y + 2 + 3(1 - y)
Use the distributive property on the 3(1 - y) part.
3 • 1 = 3
3 • -y = -3y
5 + 6y = 9y + 2 + 3 + -3y
Combine like terms.
The like terms are:
9y and -3y
2 and 3
9y - 3y = 6y
2 + 3 = 5
5 + 6y = 6y + 5
This can not be simplified further, since doing so would only result in 0.
So no matter what y is, this is true.
If you were to fully simplify this, it would be 0 = 0.
Hope this helps!